2015
DOI: 10.5120/21220-3960
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Feature Extraction Methods of Malware Detection

Abstract: Recent years have encountered massive growth in malwares which poses a severe threat to modern computers and internet security. Existing malware detection systems are confronting with unknown malware variants. Recently developed malware detection systems investigated that the diverse forms of malware exhibit similar patterns in their structure with minor variations. Hence, it is required to discriminate the types of features extracted for detecting malwares. So that potential of malware detection system can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…Since there is no classification system available in literature for the above mentioned categories, so we have given comparison of our system with malware vs benign classifiers [11,12], which are much simpler. Table 4 gives the classification accuracy and FPR for these five 2-class problems, and Table 5 gives the accuracy & FPR for 2 class classifier problems (Malware vs Benign) [11,12]. These classification results indicate that there exist class specific signatures for every class which can be extracted manually by thorough inspection.…”
Section: Classification Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is no classification system available in literature for the above mentioned categories, so we have given comparison of our system with malware vs benign classifiers [11,12], which are much simpler. Table 4 gives the classification accuracy and FPR for these five 2-class problems, and Table 5 gives the accuracy & FPR for 2 class classifier problems (Malware vs Benign) [11,12]. These classification results indicate that there exist class specific signatures for every class which can be extracted manually by thorough inspection.…”
Section: Classification Results and Analysismentioning
confidence: 99%
“…Gandotra et al [10] gave extensive survey of various researches related to malware classification. Ranveer and Hirai [11] categorized various features used in the malware detection systems. They have compared features of static, dynamic and hybrid type.…”
Section: Introductionmentioning
confidence: 99%
“…Those metrics are discovered during malware interactions with the underlying system. Such metrics can be utilized to detect a possible attack [17].…”
Section: Related Workmentioning
confidence: 99%
“…Several previous studies have shown promising results using ML algorithms to detect malware [16] or to differentiate between different families of malware [9]. There are two common approaches to extract features from malware: static analysis and dynamic analysis [6].…”
Section: Related Workmentioning
confidence: 99%